АҚМОЛА ОБЛЫСЫНЫҢ «ЕНБЕК» ЖШС ЖАҒДАЙЫНДА ЛАКТАЦИЯ КЕЗЕҢІНДЕГІ СИЫРЛАРДА СУБКЛИНИКАЛЫҚ МАСТИТТІ ДИАГНОСТИКАЛАУ - Г. Мержақыпова; Ж. Кемешов; А. Карамян; А. Бакбергенова; Г. Ергешбаева; А. Өмірәлі (Animal Health and Biosafety, 2026)
There are many problems that reduce the volume of production in dairy farms. Of these, the most inconspicuous and most costly is subclinical mastitis. The cow looks healthy outwardly, there is no visible change in the wind, but it is during this period that the quality of milk decreases, and the infection begins to spread inside the herd. If the disease is detected late on the farm, the subsequent loss is not limited to treatment. Technological indicators of milk deteriorate, productivity decreases, and in some cases animals have to be removed from the farm ahead of time. The study was conducted in the conditions of Enbek LLP in Akkol District of Akmola region. The goal is a comprehensive assessment of the effectiveness of diagnostic methods used to identify subclinical mastitis in dairy cows. In the study, individual milk samples were taken from each quarter of the udder. For diagnostics, Kerba Test," Kenotest", clinical examination of the udder, calculation of somatic cells using the" Somatos-Mini " analyzer and bacteriological study were used. As a result of Express tests, positive reactions characteristic of latent inflammation were recorded in a number of cows. An increase in the number of somatic cells confirmed the presence of an inflammatory process. Although in some cases the appearance of the udder was normal, laboratory indicators showed that the disease was progressing. During a bacteriological study, Staphylococcus aureus was identified as the main pathogen. As well as Streptococcus agalactiae, Escherichia coli, Proteus spp. and Candida spp. separated. The results obtained showed that it is not enough to rely on just one Test. It is possible to accurately determine subclinical mastitis only if Express methods, determination of the number of somatic cells and microbiological research are combined. Detection of the disease at an early stage allows you to limit the spread of infection in the herd, maintain the quality of milk and reduce production costs.